Action learning and the pedagogy of professional doctorates. Issue 2 (13th May 2014) - Bourner, Tom; Simpson, Penny
Abstract : Purpose: – This paper is about action learning and the pedagogy of professional doctorates. The purpose of this paper is to explore the pedagogical problems of the relatively new professional doctorates and consider whether action learning offers potential solutions. Design/methodology/approach: – This conceptual paper seeks to answer the question: how good is the fit between the learning processes of action learning and the learning goals of professional doctorates? Findings: – The main conclusions of the paper are that action learning can support the learning of students enroled on professional doctorates by helping them realise the following three key learning outcomes, namely, the capacity to contribute to the advancement of knowledge, that is relevant to professional practice; their own personal and professional capabilities as practitioners; and their capacity to bring about change that directly enhances professional practice, i.e. they can make a direct contribution to professional practice, e.g. through some successful project that they undertake. Research limitations/implications: – While this paper is not based on research, the main implication is that action learning can offer a valuable pedagogic approach in supporting the learning of professional doctoral candidates towards their goal of making an original contribution to the advancement of professional practice. Practical implications: – A second implication is the need for many of those university academics responsible for leading and managing professional doctorates to become more familiar with the theory and practice of action learning. A third implication is the appreciation of the need to weigh up cost against the benefits of using action learning as a pedagogic process on professional doctorates. Originality/value: – This conceptual paper is original as it explores the fit of action learning with pedagogic issues of professional doctorates.